ACCOUNTING AND DISTRIBUTION TECHNIQUES AS VOLUNTARY DEVICES TO ELIMINATE ABUSES IN MARKETING. - Sawyer, Albert E. (The Accounting Review, 1939)
Abstract This article considering the accounting and marketing techniques which flow from state and federal laws affecting price and pricing policies in the U.S. It is needless to stress the fact that government intervention in business has increased greatly in recent years. This trend is likely to continue to increase, but the rate of that increase can and will be modified by the extent to which business itself puts its own house in order. It is necessary at this point to lay the foundation for an important distinction which needs to be drawn between true open-price reporting and the variety of price reporting which prevailed in many instances during the National Recovery Administration. Since many trade associations arise out of the state of business depression within an industry, it is not unnatural to find that their spirit and purpose is strongly defensive. To those who enter upon an Open-Price Association under the conviction that they have joined hands to fight a common enemy, the legal requirement that all price data be made available to buyers and sellers alike comes as a rude shock. It is tantamount to an order to disclose everything to the enemy, and is hardly consistent with usual defense tactics.